2000
DOI: 10.1016/s0893-133x(99)00129-3
|View full text |Cite
|
Sign up to set email alerts
|

Allostasis and Allostatic Load Implications for Neuropsychopharmacology

Abstract: The primary hormonal mediators of the stress response, glucocorticoids and catecholamines, have both protective and damaging effects on the body. In the short run, they are essential for adaptation, maintenance of homeostasis, and survival (allostasis). Yet, over longer time intervals, they exact a cost (allostatic load) that can accelerate disease processes. The concepts of allostasis and allostatic load center around the brain as interpreter and responder to environmental challenges and as a target of those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
994
0
19

Year Published

2004
2004
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,441 publications
(1,072 citation statements)
references
References 146 publications
21
994
0
19
Order By: Relevance
“…An adaptive system of allostasis (stability through change) is pivotal to keep a homeostatic balance. In healthy individuals, the body is able to cope with moderate challenges, but if the allostatic system is overactivated or maladaptive, the “allostatic load” may induce a vulnerability to disease [McEwen, 2000]. …”
Section: Discussionmentioning
confidence: 99%
“…An adaptive system of allostasis (stability through change) is pivotal to keep a homeostatic balance. In healthy individuals, the body is able to cope with moderate challenges, but if the allostatic system is overactivated or maladaptive, the “allostatic load” may induce a vulnerability to disease [McEwen, 2000]. …”
Section: Discussionmentioning
confidence: 99%
“…Early adverse life experiences, such as sexual and physical abuse and feelings of neglect, might play a significant role in determining a so-called allostatic load later in life [25]. Similarly, Heim et al [18] found that severe stress (sexual and physical abuse) early in life is associated with persistent sensitization of the HPA axis, which in turn is related to an increased risk for adulthood psychopathological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Later, the process of developing alcohol abuse was stated as the "allostasis model of alcoholism" (Koob and LeMoal 2001;Koob 2003a;Roberts et al 2000). This view of "allostasis" arose in part from a previous conceptual framework espoused by Sterling and Eyer (1988) and McEwen (1998McEwen ( , 2000. While allostasis was initially viewed as an adjustment to environmental change through the establishment of new physiological set-points (Sterling and Eyer 1988), the concept of allostatic load was introduced as a pathophysiological state related to excessive allostasis (McEwen 1998(McEwen , 2000.…”
Section: Stress During Withdrawal From Multiple Alcohol Exposures Incmentioning
confidence: 99%